Expression of Bt Protein in Transgenic Bt Cotton Plants and Ecological Fitness of These Plants in Different Habitats - Liu, Laipan; Guo, Ruqing; Qin, Qin; Fu, Jianmei; Liu, Biao (Frontiers in Plant Science, 2020)
Fitness is one of the key parameters to evaluate the effects of transgenic plants on the ecological environment. To evaluate the ecological risk of transgenic Bt cotton plants growing in different habitats, we determined the expression of the exogenous Bt gene and the fitness of transgenic and non-transgenic cotton plants in three habitats (farmland, grassland, and shrub). We observed that the expression of Bt protein in the farmland was significantly higher than that in the natural habitat, and when the growth environment was suitable, the Bt protein expression level showed a downward trend with the advancement of the growth. There were no significant differences in plant height, aboveground biomass, and seed yield between the Bt transgenic and non-transgenic cotton plants at the same growth stage under the same habitat. Nevertheless, in different habitats, the fitness of the same cotton line showed significant differences. In the farmland habitat, the plant height, aboveground biomass, and seed yield of both transgenic cotton and its non-transgenic isoline were significantly higher than that in the other two natural habitats. The results indicate that the expression of Bt protein does not increase the fitness of the parent plants and would not cause the weeding of the recipient cotton plants.